Covid 19 Sebagai Bencana Global Abad 21 Tinjauan Disaster Diplomacy - Laode Muhamad Fathun; Mega Dwifarhani (Padjadjaran Journal of International Relations, 2023)
The COVID-19 pandemic has had a significant impact on the world, in health, economic to political and socio-cultural sectors. The widespread of the corona virus has caused many conflicts between countries in health and economic crises globally. This research was conducted to explain that the pandemic experienced in the 21st century is a global disaster which has spawned a series of opportunities for cooperation between international countries to defeat the COVID-19 pandemic. This research is qualitative using the perspective of disaster diplomacy. The data collection technique is literature study with stages in the form of collecting data, selecting the data and drawing conclusions. From the research results it is known that the global disaster caused by COVID-19 does not only have a negative impact, but opens opportunities for international countries to cooperate with each other in dealing with a pandemic through disaster diplomacy. Cooperation between international countries must continue to be carried out to achieve a common goal, ending the COVID-19 pandemic.